(untitled) (Comillas Journal of International Relations, 2024)
The Jesuit missions (reducciones) with the Guarani turned out to be a kind of alternative relationship between the Spanish collective and the native, a relationship respectful of the people and their culture. This article studies the concept of reductions and the context in which they arose, how the Society had to make changes in its legislation to take them on, which was done as a temporary exception that was perpetuated. This led to the development of a network of 30 villages, the end of which was the Treaty of Limits (1750) between Spain and Portugal. It ends with some reflections on the valuation of this missionary experience and its ruins. A bibliographical selection of the existing literature has been used.